Uso de dos protocolos de sincronización modificados (co-synch® + cidr®) y su efecto en parámetros reproductivos en vaquillas de aptitud lechera. - Mendoza Muñoz, Edison Robinson (2017)
The objective of this research was to evaluate the use of two modified synchronization protocols and their effect on reproductive parameters in dairy heifers on La Poderosa farm of the Canuto parish. Three treatments were used that corresponded to different days of withdrawal of the intravaginal device, 5, 6, and 7 days respectively, each treatment consisted of a batch of 6 heifers. The variables to be evaluated were: Index of animals with obvious heat, time and duration of obvious heat, rate of return to 20-25 days post AI, conception index and cost-benefit analysis. The results were evaluated by an analysis of variance for the observations of the quantitative variables, and where there were statistical differences was verified by the Tukey test at 0.05%. There were significant differences (P <0.05) between the treatments (T3) versus (T1) and (T2), numerically it was observed that the treatment with a longer duration of estrus was T2 with an average of 8 hours, followed by T1 with 7, hours, then T3 with 6 and a half hours. In the conception index, results were obtained that in treatment 2 (6 days) was the best because of 6 heifers treated a total of 4 were in gestation, corresponding to 66%. Concluding that the most profitable treatment was the (T2) with a profit of 796.17 dollars showing that each dollar invested generates a gain of 0.18 cents, which represents an 18% profitability.